Analysis of Trace Element Concentrations of Some Lichens of Turkey - ASLAN†, ALI; APAYDIN‡, GÖKHAN; YAZICI*, KENAN; CENGIZ‡, ERHAN; AYLIKCI‡, VOLKAN; TIRASOGLU‡, ENGIN (Asian Journal of Chemistry, 2009)
In this study, concentrations of six different elements (Ca, K, Fe,Ba, Ti and Sr) were measured in twelve lichen species from two geographicallydifferent regions (Northern Anatolia: Provinces of Trabzon,Ordu, Artvin and Giresun and Eastern Anatolia: Erzurum province) inTurkey. An annular 55Fe and 241Am radioactive source was used for excitationof characteristic K X-rays using radioisotope excited energydispersive X-ray fluorescence method of multiple standard addition.The incident beam and fluorescence X-rays emitted from the target weredetected and analyzed with an Ultra-LEGe detector. Five of the sixelements (Ca, K, Fe, Ba and Ti) are available in the twelve lichen speciesliving in 12 different habitats. But, Sr is the only available element insome lichens living in some certain localities. Moreover, some lichensliving in some localities contain very high concentrations (almost 5-10folds) of Ti and Ba (for example: Ordu-Ünye Çinarsuyu, Erzurum-Köskvillage for Ti, 0.384, 0.342 %, respectively and Trabzon-Maçka, Solmaplateau for Ba and 0.306 %).